1987
DOI: 10.1021/bi00376a005
|View full text |Cite
|
Sign up to set email alerts
|

Function of pyridoxal 5'-phosphate in glycogen phosphorylase: a model study using 6-fluoro-5'-deoxypyridoxal- and 5'-deoxypyridoxal-reconstituted enzymes

Abstract: A new vitamin B6 analogue, 6-fluoro-5'-deoxypyridoxal (6-FDPL), was synthesized and characterized. This analogue, as well as 6-fluoropyridoxal (6-FPAL), 6-fluoropyridoxal phosphate (6-FPLP), and 6-fluoropyridoxine, showed positive heteronuclear 1H-19F nuclear Overhauser effects between the 5'-protons and the 6-fluorine. Apophosphorylase reconstituted with 6-FDPL showed 1% of the activity of the native enzyme in the presence of phosphite. The kinetic pattern, apparent pH optimum of activity, and the activity-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

1990
1990
1996
1996

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…The program then determines all the dissociation constants and V,,,, simultaneously by fitting all of the data at once. The values were similar to those reported previously (Parrish et al, 1977;Chang et al, 1983Chang et al, , 1987 except for those for Glc-I-P. The K,y and a K , values were reported to be 18 and 22 mM, respectively (Chang et al, 1983).…”
Section: Kineticssupporting
confidence: 90%
See 4 more Smart Citations
“…The program then determines all the dissociation constants and V,,,, simultaneously by fitting all of the data at once. The values were similar to those reported previously (Parrish et al, 1977;Chang et al, 1983Chang et al, , 1987 except for those for Glc-I-P. The K,y and a K , values were reported to be 18 and 22 mM, respectively (Chang et al, 1983).…”
Section: Kineticssupporting
confidence: 90%
“…Furthermore, "F-NMR spectra of the bound fluorophosphate activator also showed that no change in its ionization state occurred on binding or during catalysis (Chang et al, 1983), a result not in accord with a role for the cofactor 5"phosphate as a proton donor in catalysis. Based on these results and other results from kinetic and 19F-NMR experiments of GPb reconstituted with 6-fluorinzted PL and DPL, Chang et al (1987) suggested that the cofactor 5'-phosphate is mainly a structural determinant holding other groups in the correct orientation for catalysis. PL-GPb provides a good enzyme derivative to study possible functions of the cofactor 5"phosphate in GP catalysis (Chang et al, 1983(Chang et al, , 1987.…”
mentioning
confidence: 65%
See 3 more Smart Citations